Os processos estruturais e os litígios ambientais de despoluição hídrica : uma análise do caso County of Maui v. Hawaii Wildlife Fund, et al. - Linke, Micaela Porto Filchtiner (2022)
The present scientific research work aimed to deepen the study on the application of structural procedures to environmental litigation, whose object is hydric pollution, analyzing the decision of the Supreme Court of the United States of America in 2020 in the case County of Maui v. Hawaii Wildlife Fund, et al. Through a hypothetical-deductive approach and a comparative procedure, it focused on the similarities and identities between the characteristics of the structural procedures and the characteristics of the environmental cases, seeking to verify the compatibility between them. For that, it proceeded with a bibliography review on the characteristics of the structural procedures and on the characteristics of the environmental litigation, focusing on those that deal with pollution of bodies of water. With this, it was stated that structural procedures are characterized by their prospective objective of reforming a state of non-conformity and are commonly imbued with complexity and multipolarity, requiring a flexible and plastic procedure in order to adapt to the peculiarities of the conflict , as well as it was asserted that environmental litigation is often characterized by complexity and by the need for prospective solutions, as it is targeted to promoting a balanced environment for current and future generations, being the consideration of the environment as interconnected and interdependent ecosystems an intrinsic challenge to it. Having made these inferences, it is concluded that structural procedures are adequate to deal with environmental cases of polluted water, given the identity of characteristics between them, as structural procedures prove to be potentially capable of enabling an effective and fair solution to the cases in question, being a legitimate instrument for the feasible improvement of systems that promote the current and prospective implementation of fundamental values linked to a balanced environment.